Devising an Appropriate Strategy for Capacity Building of a National Monitoring and Evaluation System : Lessons from Selected African Countries - Lahey, Robert (World Bank, Washington, DC, 2015)
This note examines key stages of national monitoring and evaluation systems’ (NMESs) development in different country contexts and argues for tailored approaches to building M and E capacities. The development of NMESs rests on four building blocks - vision of leadership, an enabling environment, capacity to supply and analyze M and E information, and capacity to demand and use M and E information. Developing countries can differ significantly in their performance along these four dimensions - some have virtually no NMES, while others are at a much more advanced stage where reliable and timely M and E information is generated and used. Most developing countries likely fall in between. Using the example of five African countries, this note discusses the differences and similarities in capacity-building needs for countries at different levels of NMES development.